Highly crystalline LiCuXFe1−XPO4 nanoparticles synthesized by high temperature thermal decomposition: a morphological and electrical transport study. (25th July 2016) - Martinez, P; Ruiz, F; Curiale, J; Vasquez Mansilla, M; Zysler, R D; Dada, L; Moreno, M S; Rodríguez, L; Fregenal, D; Bernardi, G; Lima, E
Abstract: In this work, we report the morphological and electrical characterization of highly crystalline L i C u X F e 1 − X P O 4 nanoparticles synthesized via the high-temperature (380 °C) thermal decomposition of organometallic precursors. The mean diameter of the studied nanoparticles was 30–40 nm. The Cu/Fe relations of 0, 0.001 and 0.042 for the three studied samples were obtained via particle-induced x-ray emission spectroscopy. Crystallographic and morphological studies were performed using x-ray diffraction, transmission electron microscopy and high-resolution transmission electron microscopy techniques. We investigated the effects of incorporating copper on the electric transport properties of this highly crystalline nanometric system using impedance spectroscopy and DC transport techniques. The experimental evidence allowed us to conclude that in the frequency range f < 1 kHz the transport is dominated by the diffusion of Li and the presence of Cu atoms in the systems hinders this transport mechanism, despite the high crystallinity of the system.